Dynamics of FABP4 and CTRP3 biomarkers in patients with acute myocardial infarction and type 2 diabetes mellitus - Koteliukh, Mariia (ScienceRise: Medical Science, 2022)
The aim of the work was to study the characteristics of adipokine metabolism based on the analysis of fatty acid binding protein 4 (FABP4) and C1q/tumour necrosis factor-related protein-3 (CTRP3) levels and their dynamics in non-diabetic and diabetic patients with cardiovascular (CV) complications of acute myocardial infarction (AMI). Materials and methods. The study was carried out between 2018 and 2020 and involved 134 AMI patients with or without type 2 diabetes mellitus (DM) aged 59.00 [52.75; 66.00] years. The control group consisted of 20 healthy individuals with the mean age of 56.50 [48.50; 61.75] years. The serum levels of FABP4 and CTRP3 were measured by enzyme-linked immunosorbent assay on days 1 and 10 of hospital stay. Results. The mean levels of FABP4 were elevated on day 1 in AMI patients with type 2 DM (group II) compared to those in AMI patients (group I) and the control individuals (p<0.05). The FABP4 concentrations on day 10 were 7.68 [6.42; 8.42] ng/ml and 8.31 [6.92; 9.63] ng/ml (p<0.05) in groups I and II, respectively. The CTRP3 levels were lower in group II on day 1 as compared to those in group I and the control group patients (p<0.001). After 10 days, the levels of CTRP3 were 287.56 [271.48; 300.58] ng/ml and 262.01 [225.32; 288.84] ng/ml) (p<0.001) in groups I and II, respectively. In the presence of early AMI complications in diabetic patients, the levels of FABP4 remained elevated on day 10, and the levels of CTRP3 were low compared to those in diabetic patients without AMI complications (p<0.05). Conclusions. The characteristics of adipokine metabolism in AMI patients have been revealed: the worsened imbalance in adipokine metabolism in type 2 DM due to the difference in FABP4 and CTRP3 levels. Special mention should be made of severely deteriorated adipokine metabolism in diabetic patients with CV complications